MODEL PEMBELAJARAN MATEMATIKA ONLINE BERBASIS MOBILE LEARNING MELALUI WAP (WIRELESS APPLICATION PROTOCOL) UNTUK SEKOLAH MENENGAH ATAS - Setyowibowo, Sigit (DINAMIKA DOTCOM, 2010)
Math was always regarded as the most intimidating subject of learning by the students. For that we need the development of various teaching methods, devices and apparatuses are needed to support the process of teaching and learning activities that teach not only targets are met but the discussion of student learning in the eye is also fulfilled. Hopefully with the online mathematical learning model using WAP-based mobile learning as an alternative media is expected to provide facilities and Visualization of knowledge so that knowledge becomes attractive and the young understood.Â Keywords: Matematika ,Online, WAP (Wireless Aplication Protocol)Â